Morphine Use in Cancer Surgery - Afsharimani, Banafsheh; Cabot, Peter J.; Parat, Marie-Odile (Frontiers in Pharmacology, 2011)
Morphine is the core of perioperative pain management. However, when it comes to cancer surgery the possibility that this drug might affect tumor recurrence and metastasis has raised concerns. The results of two recent retrospective clinical trials indicated that regional anesthesia/analgesia might be beneficial in prostate and breast cancer surgery. It was proposed that morphine could be responsible for the higher recurrence and mortality rate observed in the general anesthesia/opioid analgesia groups. Nevertheless, the results of several other retrospective studies and one randomized prospective trial failed to confirm any advantage for regional anesthesia/analgesia over general anesthesia and opioid analgesia. Moreover laboratory data on the effect of morphine on cancer are contradictory, ranging from tumor-promoting to anti-tumor effects. Considering that surgical stress and pain promote the recurrence and spread of cancer, choosing a proper analgesic strategy is of high significance. Although the question of whether morphine causes any harm to cancer patients remains unanswered, alternative analgesic regimens could be used concomitant to or instead of morphine to limit its potential adverse effects.